STEPS OF ORGANIZING THE CONTROL ON THE INSURANCE ACTIVITY IN UZBEKISTAN - Nuritdinova Vasila Shavkatovna; Sharipov Komiljon Karimovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article outlines the steps for organizing the control of insurance activities in the Republic of Uzbekistan. It also shows several tasks that need to be solved to further improve the control of insurance activities.